Data supporting "A novel dielectric sensor for process monitoring of carbon fibre composites manufacturing" - Tifkitsis, Konstantinos; Skordos, Alexandros A. (Cranfield University, 2019)
Flow sensor validation: includes the lineal sensor results during RTM processing and comparison with visual monitoring data-Cure sensor: includes the Cure sensors results of isothermal runs of neat resin and VART and the comparison with existing models.
Keywords: 'carbon fibres'; 'curing'; 'resin transfer moulding'; 'RTM'; 'process monitoring'; 'Aerospace Materials'; 'Aerospace Engineering'